The Effect of Career Development and Organizational Commitment on Employee Performance Through Extrinsic Motivation at PT Bank Sumut Kantor Cabang Koordinator Medan - Nurul Huda Chasanah; Ritha F. Dalimunthe; Prihatin Lumbanraja (International Forum of Researchers and Lecturers, 2025)
Employee performance is a strategic factor in the success of regional banking organizations that are oriented towards service and achieving business targets. However, empirical evidence at PT Bank Sumut Kantor Cabang Koordinator Medan, indicates that employee performance tends to stagnate in the